2020
DOI: 10.1093/jrr/rraa063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prostate verification with implanted gold markers in tissue surrounding the prostate and pelvic bony anatomy for external beam radiation therapy following low-dose-rate brachytherapy: a prospective clinical trial

Abstract: We aimed to investigate whether gold marker implantation in the tissue surrounding the prostate could accurately monitor setup errors during external beam radiation therapy (EBRT) following low-dose-rate (LDR) brachytherapy. Thirty-eight patients had confirmed intermediate- or high-risk prostate cancer and received EBRT following LDR brachytherapy. In >175 computed tomography imaging sessions, the average values of the weekly setup error during EBRT to the prostate centroid at the time of gold marker ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…As a clinical result, Kaneda et al 83 reported a significantly lower positioning error when performing image guidance of external beam radiotherapy by matching golden fiducials instead of bone matching in a retrospective analysis of a series of 38 patients presenting intermediate-or high-risk prostate cancer and received EBRT following LDR brachytherapy. Interestingly, Brown et al 84 analyzed patient's experiences and preferences of imageguidance procedures, exploring the different perceptions about the placement of fiducial markers versus the use of ultrasound for image guidance of radiotherapy.…”
Section: The Most Intriguing Inter-and Intra-fractional Treatment Aids For Modern Gating Of the Image-guided Radiotherapy: Fiducial Markementioning
confidence: 99%
“…As a clinical result, Kaneda et al 83 reported a significantly lower positioning error when performing image guidance of external beam radiotherapy by matching golden fiducials instead of bone matching in a retrospective analysis of a series of 38 patients presenting intermediate-or high-risk prostate cancer and received EBRT following LDR brachytherapy. Interestingly, Brown et al 84 analyzed patient's experiences and preferences of imageguidance procedures, exploring the different perceptions about the placement of fiducial markers versus the use of ultrasound for image guidance of radiotherapy.…”
Section: The Most Intriguing Inter-and Intra-fractional Treatment Aids For Modern Gating Of the Image-guided Radiotherapy: Fiducial Markementioning
confidence: 99%